Evaluation of FamMed essentials: a blended-learning program for capacity building of general practitioners in Pakistan - Unab I Khan; Hamida Farazdaq; Azra Naseem; Waseem Suleman; Sania Saleem; Muskaan Abdul Qadir; Komal Fatima (BMC Medical Education, 2024)
Abstract Background To provide access to primary care and universal health coverage, Pakistan requires 60,000 trained family physicians by 2030. At present, most primary care is provided by general practitioners (GPs) who do not have any post-graduate training. Empowering GPs through competency–based programs, that strengthen their knowledge and skills, may be a cost-effective strategy for improving healthcare quality. We describe the development and evaluation of FamMed Essentials, a modular, blended-learning program to improve clinical knowledge and skills of GPs. Methods This is a mixed method study. We used the CIPP (content, input, process and product) framework for course development and evaluation. We describe the steps used in content development, strategies for teaching and assessments, and evaluation of strengths and weaknesses of the program. In depth focus group discussions were conducted to gather insight on participants’ and faculty’s perceptions regarding the program’s effectiveness. Results Of the 137 participants who have completed the program, 72% were women and 49% had been practicing for more than five years. We saw a significant improvement in knowledge across all modules ( p = < 0.001) and perceived confidence in clinical skills ( p = < 0.001). An objective assessment showed participants’ competence in patient management. Participants reported a high level of satisfaction (4.4 ± 0.83 on a 5-point Likert Scale). Focus group discussions revealed a positive impact on clinical practice. Flexibility and use of different teaching and learning strategies were additional strengths. In addition, participants reported an interest in further training. Power outages were highlighted as a major challenge. Conclusion In resource-constrained health systems, a modular, blended-learning, competency-based program is helpful to upgrade GPs knowledge without impacting their busy schedules. Accreditation of such programs and provision of a career trajectory for the trained GPs are pivotal to expansion of such initiatives.